Cordycepin Ameliorates Nonalcoholic Steatohepatitis by Activation of the AMP‐Activated Protein Kinase Signaling Pathway. Issue 2 (26th August 2021) - Lan, Tian; Yu, Yang; Zhang, Jing; Li, Haonan; Weng, Qiqing; Jiang, Shuo; Tian, Song; Xu, Tonghao; Hu, Sha; Yang, Guizhi; Zhang, Yan; Wang, Weixuan; et al.
Abstract : Background and Aims: Nonalcoholic fatty liver disease, especially nonalcoholic steatohepatitis (NASH), has become a major cause of liver transplantation and liver‐associated death. NASH is the hepatic manifestation of metabolic syndrome and is characterized by hepatic steatosis, inflammation, hepatocellular injury, and different degrees of fibrosis. However, there is no US Food and Drug Administration–approved medication to treat this devastating disease. Therapeutic activators of the AMP‐activated protein kinase (AMPK) have been proposed as a potential treatment for metabolic diseases such as NASH. Cordycepin, a natural product isolated from the traditional Chinese medicine Cordyceps militaris, has recently emerged as a promising drug candidate for metabolic diseases. Approach and Results: We evaluated the effects of cordycepin on lipid storage in hepatocytes, inflammation, and fibrosis development in mice with NASH. Cordycepin attenuated lipid accumulation, inflammation, and lipotoxicity in hepatocytes subjected to metabolic stress. In addition, cordycepin treatment significantly and dose‐dependently decreased the elevated levels of serum aminotransferases in mice with diet‐induced NASH. Furthermore, cordycepin treatment significantly reduced hepatic triglyceride accumulation, inflammatory cell infiltration, and hepatic fibrosis in mice. In vitro and in vivo mechanistic studies revealed that a key mechanism linking the protective effects of cordycepin were AMPK phosphorylation–dependent, as indicated by the finding that treatment with the AMPK inhibitor Compound C abrogated cordycepin‐induced hepatoprotection in hepatocytes and mice with NASH. Conclusion: Cordycepin exerts significant protective effects against hepatic steatosis, inflammation, liver injury, and fibrosis in mice under metabolic stress through activation of the AMPK signaling pathway. Cordycepin might be an AMPK activator that can be used for the treatment of NASH.